The Relationship between Smartphone Dependence and Nomophobia (No Mobile Phone) Anxiety at SMA Negeri 1 Tapa, Bone Bolango Regency - Nur Azizah Mahmud; Pipin Yunus; Rini Asnawati; Sabirin B. Syukur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The increasing use of smartphones among teenagers has the potential to cause dependency and psychological disorders, one of which is nomophobia anxiety (no mobile phone phobia). This study aims to determine the relationship between smartphone dependence and nomophobia anxiety in students of SMA Negeri 1 Tapa, Bone Bolango Regency. This study uses a crosssectional design. The sample amounted to 52 students who were selected using the proportionate stratified random sampling technique. The instruments used were the Smartphone Addiction Scale (SAS) and the Nomophobia Questionnaire (NMP-Q). The results showed that most of the respondents experienced smartphone dependency in the high category, namely 46 students (82%), while the low category was 6 students (12%). This study concludes that wise management of smartphone use is necessary to prevent nomophobia anxiety in adolescents.